2021
DOI: 10.1186/s12711-021-00641-2
|View full text |Cite
|
Sign up to set email alerts
|

New residual feed intake criterion for longitudinal data

Abstract: Background Residual feed intake (RFI) is one measure of feed efficiency, which is usually obtained by multiple regression of feed intake (FI) on measures of production, body weight gain and tissue composition. If phenotypic regression is used, the resulting RFI is generally not genetically independent of production traits, whereas if RFI is computed using genetic regression coefficients, RFI and production traits are independent at the genetic level. The corresponding regression coefficients ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…RFI in the RRM was higher both at the start and end of the test period, which demonstrated the different genetic backgrounds in pig growth. The same tendency of the heritability estimates during the whole process were also reported (Shirali et al, 2017b;Coyne et al, 2017;David et al, 2021). A permanent environmental effect was also included in our RRM models, and the estimates of permanent environmental variance changed gently, which indicated that RFI was less influenced by permanent environmental effects in our study.…”
Section: Discussionsupporting
confidence: 77%
“…RFI in the RRM was higher both at the start and end of the test period, which demonstrated the different genetic backgrounds in pig growth. The same tendency of the heritability estimates during the whole process were also reported (Shirali et al, 2017b;Coyne et al, 2017;David et al, 2021). A permanent environmental effect was also included in our RRM models, and the estimates of permanent environmental variance changed gently, which indicated that RFI was less influenced by permanent environmental effects in our study.…”
Section: Discussionsupporting
confidence: 77%
“…These animals were from seven generations of a divergent selection experiment for RFI applied at the end of each test period (110 kg) [1]. Animal management and phenotype measurements are described in David et al [32] and Huynh-Tran et al [19]. The numbers of animals and records per low (LRFI), high RFI (HRFI) lines and generation are in Additional file 1: Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…The correlations between SBV l and u ySBV l were slightly lower but still large for SBV 1 (0.92 and 0.95 for LRFI and HRFI, respectively) and SBV 2 (0.94 for both lines), but lower for SBV 3 (0.78 for both lines). Since the first two SBV have been identified as sufficient to select for a desired trajectory pattern of RFI over time in pigs [32], using the model on summarized phenotypes seems a good alternative (similar accuracy with less computing time) to select for RFI trajectories in routine evaluation.…”
Section: Pedigreementioning
confidence: 99%
“…In a previous study [48], we considered the average estimate of α t during the evaluated period and not the daily estimates, and obtained a lower heritability (0.16 ± 0.05) but this was based on a different dataset. For RFI, David et al [49] reported heritabilities ranging from 0.19 ± 0.06 to 0.28 ± 0.06, using an RR model for weekly estimates of RFI over 10 weeks in pigs.…”
Section: Estimation Of the Genetic Variance Of The Allocation Coeffic...mentioning
confidence: 99%